2021
DOI: 10.1007/s40243-021-00188-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the thermal degradation, moisture absorption characteristics and antibacterial behavior of natural insulation materials

Abstract: The demand for natural insulation materials is increasing with special attention to the use of such materials for exploiting renewable energy. Natural insulation materials tremendously influence the sustainability development and energy efficiency enhancement in the buildings. Natural fibers from animal’s origin absorb great amount of moisture on exposed to the environment which significantly affects the performance and thermal insulation properties. The thermal degradation of such material strongly influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The use of renewable energy as a source of electricity or heat generation is a sector worth paying attention to because of the high energy demands of high-rises and their significant surface area exposed to solar radiation [18]. Reducing reliance on fossil fuels as a source of energy generation may also be greatly aided by the use of renewable energies in HRBs that already exist, particularly residential ones.…”
Section: Renewable Energiesmentioning
confidence: 99%
“…The use of renewable energy as a source of electricity or heat generation is a sector worth paying attention to because of the high energy demands of high-rises and their significant surface area exposed to solar radiation [18]. Reducing reliance on fossil fuels as a source of energy generation may also be greatly aided by the use of renewable energies in HRBs that already exist, particularly residential ones.…”
Section: Renewable Energiesmentioning
confidence: 99%
“…Fibrous materials, such as glass/rock wool and natural fibers, and highly porous materials, such as foams of polymers, aluminium, and cement are often used as sound‐absorbing materials 1 . However, glass/rock wools are harmful to health and may be carcinogenic too 2 thus, natural fibers and polymer foams are gaining attention as sound‐absorbing materials. The sound absorption coefficient is used to evaluate the efficiency of noise reduction for sound‐absorbing materials, and the coefficient value is affected by the closed cell to open cell ratio, porosity and pore size distribution in the material 1,3–7 …”
Section: Introductionmentioning
confidence: 99%
“…Using natural materials for insulation such as sheep wool, goat wool, and horse mane is one of the best ways to reduce greenhouse gases and provide better thermal comfort. Due to their porous structure and low density (for example, goat wool has a density of 269.874 kg/m 3 ), natural materials also have good acoustic properties [13][14][15]. Ayaz et al showed that natural materials have better environmental aspects and efficiency than conventional materials.…”
Section: Introductionmentioning
confidence: 99%